Practices, Efficacy, and Reported Side Effects Associated with Isotretinoin Treatment in Palestine - Abukhalil AD; Yousef M; Ammar M; Jaghama W; Al-Shami N; Naseef HA; Rabba AK (Patient Preference and Adherence, 2024)
Abdallah Damin Abukhalil, Mai Yousef,* Marwa Ammar,* Weam Jaghama,* Ni’meh Al-Shami, Hani A Naseef, Abdullah K Rabba Department of Pharmacy, Faculty of Pharmacy, Nursing, and Health Professions, Birzeit University, West Bank, State of Palestine*These authors contributed equally to this workCorrespondence: Abdallah Damin Abukhalil; Ni’meh Al-Shami, Pharmacy Department, Faculty of Pharmacy, Nursing and Health Professions, Birzeit University, West Bank, State of Palestine, Email adkhalil@birzeit.edu; nemaashami86@gmail.comBackground: Isotretinoin is a commonly prescribed medication for the treatment of acne. It is associated with serious side effects that require monitoring and adherence by patients and healthcare providers. No studies have been conducted in Palestine to explore isotretinoin prescribing and utilization.Objective: This study aims to evaluate the current clinical practices, adherence to clinical guidelines, efficacy, and reported side effects associated with Isotretinoin treatment in Palestine.Methods: A descriptive cross-sectional online questionnaire-based study using social media platforms (eg, Facebook and Telegram) was conducted among Birzeit University students in April 2023. This study included participants aged ≥ 18 years with a history of isotretinoin treatment; subjects with incomplete data were excluded. Statistical significance was set at P < 0.05. SPSS version 27 was used for data analysis.Results: A total of 548 participants were included in the study, the majority of most of whom were female (96%). The most predominant side effects were cracked, dry lips and xeroderma (96.2%). Moreover, 12% of participants had depression. Most respondents were educated about medication side effects and only 39.1% were counseled about blood donation. Of the 59 sexually active women, only 4 (6.8%) were asked for a recent pregnancy test. A total of 60.2% of dermatologists adhered to the American Academy of Dermatology (AAD) guidelines, and 48.7% ordered the required laboratory tests before initiating isotretinoin treatment. Only 1.7% of pharmacists followed the FDA-suggested protocols for dispensing isotretinoin to childbearing females.Conclusion: Adherence to isotretinoin safety prescribing protocols to provide patient education, monitoring, and ordering of laboratories to ensure patient safety can be improved by adapting policies and protocols in pharmacy and medical practice in Palestine to monitor and enforce adherence when prescribing, dispensing, or taking high-risk medications.Keywords: isotretinoin, acne, guidelines, adherence, side effects